Effectiveness of Peer Education Method in Increasing Knowledge and Attitude Towards HIV/AIDS Prevention among Students in Samarinda - Yuliani Winarti; Rini Ernawati (IJNP (Indonesian Journal of Nursing Practices), 2019)
Background: The rise of HIV/AIDS cases on teenagers aged 15 to 24 years old has reached 25%. Inadequate knowledge regarding HIV/AIDS has been particular issue contributing to the rise of the cases.Objective: This study aims to find out the effectiveness of peer education methods on knowledge and attitudes regarding HIV/AIDS prevention in students of SMK Kesehatan in Samarinda.Method: This study is a quasi-experimental design with a non-equivalent control group of pre-test and post-test. The sample of the study was 60 students of SMK Kesehatan in Samarinda, selected through purposive sampling, and it was divided into an experimental group that was exposed to the treatment of the peer education method, also, the other 30 students in the control group were only given a module.  Data analysis used paired t-test with a significant level of p = 0.05.Result: The result found significant differences before and after intervention in intervention groups between pre and post-test of knowledge (t=-3.83, p= 0.01) and attitudes (t=-4.54, p=0.00). A significant increase in knowledge and attitudes in the treatment group was higher than the control group.Conclusion: The peer education method is effective to increase the knowledge and positive attitudes of the students of SMK Kesehatan in Samarinda.